Periprosthetic Fracture of Greater Trochanter in Total Hip Replacement Stemming from Pin Site Placement in Navigation-Assisted Surgery - Ava Brozovich; David R. Lionberger (Case Reports in Orthopedics)
Surgeons are looking to use computer computer-assisted surgery (CAS) in total hip arthroplasty (THA) in order to quantify leg length measurement, angular cup placement, and enhance stability to provide enhanced accuracy in implant placement. As a result, CAS in THA is gaining popularity. This technology employs the use of pins and provides the surgeon with real-time feedback on positioning intraoperatively. Previous total knee arthroplasty (TKA) literature has reported pin-associated complications such as infections, neuropraxia, and suture abscess. To our knowledge, there have been reports of tibial stress fracture after CAS TKA, but this is the first report of a pin causing fracture of the greater trochanter leading to dislocation in THA. Further studies may be warranted to optimize pin placement for trackers to prevent fractures of the greater trochanter.